2016
DOI: 10.4212/cjhp.v69i6.1607
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Apixaban Dosing to Prevent Stroke in Patients with Atrial Fibrillation: A Pilot Study

Abstract: Background:The ARISTOTLE study investigated apixaban, at a dose of 5 mg PO bid, for the prevention of stroke in patients with atrial fibrillation; however, it has been noted anecdotally that many patients are receiving 2.5 mg PO bid, despite being eligible for the full dosage. A recent study examining the use of dabigatran and rivaroxaban found that many patients were receiving these medications inappropriately; however, a literature search conducted in April 2016 showed that apixaban had not been formally stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Accordingly, and in agreement with the mentioned studies, more patients were being prescribed with a reduced dose of the factor Xa inhibitors than those who met the reduction criteria . Choosing lower doses reflects a greater concern by the physician to avoid bleeding complications rather than thromboembolic events …”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Accordingly, and in agreement with the mentioned studies, more patients were being prescribed with a reduced dose of the factor Xa inhibitors than those who met the reduction criteria . Choosing lower doses reflects a greater concern by the physician to avoid bleeding complications rather than thromboembolic events …”
Section: Resultssupporting
confidence: 62%
“…It is important to note that, in ORBIT‐AF registry II (Outcomes Registry for Better Informed Treatment of Atrial Fibrillation phase II), apixaban was the most commonly underdosed DOAC . Also, these findings are corroborated by Barra et al study and also by a small Canadian study, where a total of 47 patients were included, among whom 25 (53%) were receiving apixaban inconsistent with the ARISTOTLE trial and the product monograph.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…36 The NOACs are typically labeled for a standard dose and a reduced dose regimen, according to specific criteria for stroke prophylaxis in atrial fibrillation and in some countries for VTE. Retrospective medical record reviews have shown a high degree of inappropriate dose selection, even in hospitals, 37,38 with many of those patients receiving a suboptimal dose. This may also be true for the patients with VTE and is thus another explanation for breakthrough events.…”
mentioning
confidence: 99%